The Effect of Giving Bio Fertilizer and Foliar Fertilizer on the Growth and Yield of Celery (Apium graviolens) - Wiwik Yunidawati; Riyanti Riyanti; Mazlina Mazlina (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
This study aims to determine the effect of bio fertilizers and foliar fertilizers on growth and yield of celery (Apium graviolens). This research was conducted at the Experimental Garden of the Faculty of Agriculture, Amir Hamzah University, Medan, Medan Estate Village, Percut Sei Tuan District with a height of ± 25 meters above sea level, which was conducted from May to July 2020. This study used a factorial Randomized Block Design with two factors studied, namely the first factor was the concentration of bio fertilizer Impro Tanotec (H), which consisted of 4 levels, namely H0 (0 ml/l water), H1 (1,5 ml/l water), H2 (2,5 ml/l water), H3 (3,5 ml/l water), and the second factor is the concentration of foliar fertilizer Growmore (D) which consists of 4 levels, namely D0 (0 gr/lwater), D1 (1 gr/l water), D2 (2 gr/l water), and D3 (3 gr/l water). Parameters observed included plant height (cm), number of leaves, number of stalks, root length (cm), and fresh weight per plant. (gr). The results showed that the concentration of bio fertilizer had a very significant effect on plant height at the age of 20, 40, and 60 days after planting, the number of leaves at the age of 20, 40, and 60 days after planting, the number of stalks at the age of 40 and 60 days after planting, root length, and fresh weight per plant, but did not significantly affect the number of stalks at the age of 20 days after planting. The best bio-fertilizer concentration was obtained in the H3 treatment (3.5 ml/l water). The concentration of foliar fertilizer had a very significant effect on plant height at the age of 20, 40, and 60 days after planting, the number of leaves at the age of 20, 40, and 60 days after planting, the number of stalks at the age of 40 and 60 days after planting, and the fresh weight per plant, had a significant effect on root length, and had no significant effect on the number of stalks at the age of 20 days after planting. The best foliar fertilizer concentration was obtained in D3 treatment (3 gr/l water). The interaction between the concentration of bio fertilizer and foliar fertilizers had a significant effect on the number of leaves at the age of 40 and 60 days after planting, where the best treatment combination was obtained in the H3D3 treatment (bio fertilizer concentration 3.5 ml/l water and foliar fertilizer concentration 3 gr/l water).